Skill transfer through multi-sport play: A tennis and hockey example - Roetert, E. P.; Malmqvist, O.; Davies, K.; Way, R. (Coaching and Sport Science Review, 2021)
The concept of "skill transfer" is introduced with the sports of ice hockey and tennis as examples. Skill transfer is addressed with a backdrop and understanding that it is based on existing concepts that have been researched significantly over the past few decades. They include Physical Literacy, Early Sport Specialization and Long-Term Athlete Development. Specific commonalities and skill benefits are highlighted. This inclusive, unified approach may serve as a catalyst to a better understanding of the benefits of skill transfer as well as the benefits of learning physical activities through two sport examples on multiple surfaces.